Study of Semanggol Formation: Comparison of Porosity and Permeability in Different Depositional Environments - Gobalu, Mohhan (2016)
Semanggol Formation was formed during the Early Permian to Middle Triassic. Semanggol Formation was earlier deposited in one basin which was then detached into three different part of zone by wrench fault. The basis of this project is to update the database of Semanggol Formation. There were several studies focused in the study area, however less emphasis was taken in terms of studying the porosity and permeability of the study area. This project studies the porosity and permeability variations of two outcrops in the study area to be updated in the database. This will be done by using the poroperm equipment that analyzes the core plugs retrieved from the study area. The project covers in the aspects of geological mapping skills, stratigraphy logging techniques and thin section analysis. Thin section had been done to understand the texture, grain size and minerals contained. From the poroperm findings, a value for both porosity and permeability was obtained and it shows a variation in both of the outcrops. The data in this paper is vital to understand the geological relationship between the outcrops in Semanggol Formation. In context of future recommendations, geochemistry aspects of Gunung Semanggol should be researched in depth to have better understanding on the formation which makes up the petrophysical properties of the sample retrieved there.